Tuberculosis remains a major burden in systemic lupus erythematosus patients in Durban, South Africa - Al-arbi, Khaled Mohamed Sefow; Magula, Nombulelo P.; Mody, Girish M. (Frontiers in Medicine, 2023)
Objective: Infections are common in systemic lupus erythematosus (SLE), with tuberculosis (TB) being important in an endemic environment. We studied the prevalence and spectrum of TB in SLE in Durban, South Africa. Methods: A medical records review of SLE patients seen over 13-year period, and the demographic data, clinical manifestations, laboratory findings, treatment and outcome were noted. Results: There were 512 SLE patients and 72 (14.1%) had TB. Thirty (41.7%) had pulmonary TB (PTB) and 42 (58.3%) had extra-pulmonary TB (EPTB). The prevalence of TB among the different ethnic groups was 36/282 (12.8%) for Indian people, 29/184 (15.8%) Black African people, 7/26 (26.9%) admixed African people and none among the 18 White people. Comparison of the 72 SLE-TB patients with 72 SLE controls showed no difference in gender, age at SLE diagnosis and disease duration. The SLE-TB patients had a significant increase in the clinical and laboratory features of disease activity (arthritis, mucocutaneous lesions, renal involvement, vasculitis, low complement, raised ds-DNA antibodies), and cumulative prednisone use over the preceding three months. Compared to PTB, the EPTB patients were significantly younger, developed TB earlier after SLE diagnosis, and had higher disease activity. The EPTB patients also had increase in features of disease activity (renal, thrombocytopaenia, ds–DNA antibodies), and increase in ever use of intravenous methylprednisolone (IV-MP) and mycophenolate mofetil (MMF). On multivariate analysis, the independent risk factors for EPTB were ever use of MMF (p=0.003) and IV-MP (p=0.027). Analysis of the cumulative SLE criteria showed renal involvement was an independent risk factor for EPTB. The outcome was similar in both groups. Conclusion: We show an increased prevalence of TB (14.1%) and EPTB (58.3%) in SLE in an endemic area and confirm that features of disease activity and use of immunosuppressive therapy are the major risk factors. Renal involvement (as a cumulative criterion) is an independent risk factor for EPTB.